+0  
 
+1
356
2
avatar+1442 

When the expression $-5x^2+20x-17$ is written in the form $a(x+d)^2+e$, where $a$, $d$, and $e$ are constants, then what is the sum $a+d+e$?

 

 

thanks so much!

AnonymousConfusedGuy  Oct 22, 2017
 #1
avatar+1442 
+2

Please could someone respond?

AnonymousConfusedGuy  Oct 22, 2017
 #2
avatar+92788 
+3

 

-5x^2+20x-17    divide through by - 5

 

-5 ( x^2 - 4x + 17/5)

 

Take 1/2 of 4  =  2.......square it = 4.....add it and subtract it

 

-5 ( x^2 - 4x + 4 + 17/5 - 4)

 

Factor the first three terms and simplify

 

-5 [ (x -2)^2  +  17/5 - 20/5 ] 

 

-5 [ (x - 2)^2  - 3/5]

 

-5( x - 2)^2  + 3

 

a = -5   d = -2    and  e = 3

 

So

 

a + d + e  =   -5 + (-2) + 3  =   -7 + 3  =  - 4 

 

 

cool cool cool

CPhill  Oct 22, 2017

10 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.